Enhancing Computational Learning through Visual Programming Media: An Empirical Study of Academic Achievement - Sidiq, Muhammad Robby; Napitupulu, Efendi; Farihah, Farihah (PT Mattawang Mediatama Solution, 2025)
The integration of computational thinking into formal education curricula has become essential as information and communication technology continues to transform educational paradigms. This study addresses a significant challenge in computer science education, where 58% of junior high school students fail to achieve minimum learning standards in programming subjects. Objective this study to develop and evaluate the feasibility and effectiveness of visual programming learning media using Scratch 3.0 to enhance academic achievement in computer science education among seventh-grade students. This research employed a research and development approach using a 4-D model (Define, Design, Develop, Dissemination) conducted at Dr. Wahidin Sudirohusodo Junior High School over two months. The study involved comprehensive validation by three expert validators and implementation across three phases: a small group (n=5), a medium group (n=15), and field testing (n=30). The data collected included expert validation questionnaires, pre- and posttest assessments, and perception surveys, which were analyzed via descriptive statistics and t tests. Expert validation demonstrated high feasibility, with material validation scoring of 87%, media validation scoring of 83.5%, and instructional design validation scoring of 84.5%, all of which were categorized as